Biochemical response in potato cultivars to infect with Rhizoctonia solani the causal of stem canker and black scurf disease in Egypt. - Abdel-Sattar, M. A.; El-sherif, Ebtisam.M.; El-Marzouky, Hanan; Mahmoud, M.A.E. (2009)
Potato cultivars differ in their susceptibility to stem canker and black scurf disease caused by Rhizoctonia so/ani. Cultivar reactions of the most nine common commercial cultivars of potato were tested under greenhouse conditions of plant pathology research Institute, ARC-Giza. The nine tested cultivars were divided to three groups . Lady Rosella was the most susceptible cultivar followed by Monalisa and Mondial cvs. Spounta , Nicola and Hemez cultivars showed moderate susceptibility, While Draga followed by Kara and Diamond were the most resistant.
Includes references.
Summary in Arabic.
1
Keywords: Potatoes -- Disease and pest resistance; Rhizoctonia solani; Potato -- Egypt; Phytopathogenic fungi